Modelling the Thin-Layer Drying Kinetics of Untreated and Blanch-Osmotic Pre-treated Tomato Slices - Samuel Enahoro Agarry (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to investigate the effect of pre-treatment and drying temperature on the drying kinetics and nutritional quality of tomato (Lycopersicon esculantum L.) under hot air drying. Tomato samples were blanched at 80oC and osmotically dehydrated using 20% w/w sodium chloride solutions at 30oC for 20 min. The blanch-osmotic pre-treated and untreated tomato slices were dried at temperature of 40, 50, 60, 70 and 80oC, respectively in a hot air-dryer. The results showed that blanch-osmotic pre-treatment offered a higher drying rate and lower or faster drying time than untreated condition. The tomato drying regime was characteristically in the constant and falling rate period. The tomato drying rate curve showed characteristics of porous hygroscopic solids. The optimum drying temperature for tomato was found to be 60oC. Four semi-empirical drying models of Newton, Page, Henderson and Pabis, and Logarithmic were fitted to the drying data using non-linear regression analysis. The most appropriate model was selected using the coefficient of determination (R2) and root mean square error (RMSE). The Page model has shown a better fit to the drying kinetics data of tomato in comparison with other tested models. Transport of moisture during drying was described by Fick’s diffusion model application and the effective moisture diffusivity (Deff) thus estimated. The Deff at 60oC was 4.43 × 10-11m2/s and 6.33 × 10-11m2/s for blanch-osmotic pre-treated and untreated tomato slices, respectively.